Anaerobic co-digestion of agro-industrial waste for bioenergy production and digestate valorization (2025)
Anaerobic codigestion (AcoD) is the anaerobic degradation of two or more substrates with complementary properties. It is a waste treatment and recovery alternative that has shown better results than anaerobic digestion (AD). Several variables are involved in the process, such as the characteristics of the substrate, the organic load, and the temperature.